(untitled) (The Review of Diabetic Studies, 2024)
Background: Upavāsa (fasting) is a core therapeutic principle in Ayurveda, advocated for restoration of Agni, elimination of Āma, and metabolic homeostasis. During religious and intermittent fasting, cereal grains are traditionally avoided in the Indian subcontinent, creating a requirement for nutritionally adequate alternatives. Buckwheat (Fagopyrum esculentum), a gluten-free pseudo-cereal, is culturally accepted during fasting but lacks systematic Ayurvedic-pharmaceutical and nutraceutical validation in processed formulations. Objective: To develop, standardize, and nutraceutically evaluate buckwheat (Kuttu) Laddoo as a functional fasting food using Ayurvedic pharmaceutical principles and modern nutritional analysis. Materials and Methods: Buckwheat flour was processed into Laddoo using Go-ghṛta, sugar, Śuṇṭhī (dry ginger), and Maricha (black pepper) following Modaka-kalpanā principles. Organoleptic evaluation, Thin Layer Chromatography (TLC), and nutritional–mineral analysis were performed at a NABL-accredited laboratory. Results: Each 100 g of prepared Laddoo yielded 353.64 kcal energy, 56.34 g carbohydrates, 14.36 g protein, and 7.88 g fat. High mineral values were observed: iron 104.54 mg/kg, calcium 122.72 mg/kg, magnesium 72.52 mg/kg, and zinc 22.72 mg/kg. TLC revealed two prominent phytochemical spots, confirming qualitative consistency. Conclusion: Buckwheat Laddoo is a scientifically validated nutraceutical fasting food candidate with high energy, protein, and mineral content, aligned with Ayurvedic principles of Laghu, Agni-dīpana, and Kapha-Pitta śamana. It is a suitable dietary supplement during intermittent fasting.